Implicit IDA-PBC Design and Implementation for a Portal Crane System - Vidal Sandoval, Jesus Enrique (2019)
Interconnection and damping assignment passivity-based control (IDA-PBC) is a wellknown technique which regulates the behavior of nonlinear systems, assigning a target port-Hamiltonian (pH) structure to the closed-loop. In underactuated mechanical systems (UMSs) its application requires the satisfaction of matching conditions, which in many cases demands to solve partial differential equations (PDEs). Only recently, the IDA-PBC has been extended to UMSs modeled implicitly, where the system dynamics in pH representation are described by a set of differential-algebraic equations (DAEs). In some system classes this implicit approach allows to circumvent the PDE problem and also to design an output-feedback law. The present thesis deals with the design and implementation of the total energy shaping implicit IDA-PBC on a portal crane system located at the laboratory of the Control Engineering Group at TU-Ilmenau. The implicit controller is additionally compared with a simplified (explicit) IDA-PBC [1]. This algorithm shapes the total energy and avoids the PDE problem. However, this thesis reveales a significant implementation flaw in the algorithm, which then could be solved.